Adenovirus Infection in Hospitalized Children with Acute Respiratory Infection in Jordan. Issue 4 (15th December 2021) - Probst, Varvara; Rankin, Danielle A.; Haddadin, Zaid; Hamdan, Lubna; Rahman, Herdi K.; Yanis, Ahmad; Talj, Rana; Spieker, Andrew J.; Howard, Leigh; Stewart, Laura S.; Guevara, Claudia; Yepsen, Erin; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The most common clinical manifestation of adenovirus (AdV) infection is acute respiratory illness (ARI). Specific AdV species associated with ARI hospitalizations are not well defined in the Middle East. Methods: A viral surveillance study was conducted among children <2 years hospitalized in Amman, Jordan, from March 2010 to March 2013. Nasal and throat respiratory specimens were obtained from enrolled children and tested for viruses using a real-time reverse-transcription quantitative polymerase chain reaction. AdV-positive specimens were typed by partial hexon gene sequencing. Demographic and clinical features were compared between AdV detected as single pathogen versus co-detected with other respiratory viruses, and between AdV-B and AdV-C species. Results: AdV was detected in 475/3168 (15%) children hospitalized with ARI; of these, 216 (45%) specimens were successfully typed with AdV-C as the most common species detected (140/216; 65%). Children with AdV-single detection (88/475; 19%) had a higher frequency of fever (71% vs. 56%; P =0.015), diarrhea (18% vs. 11%; p=0.048), and/or seizures/abnormal movements (14% vs. 5%; p=0.003). Children with AdV co-detected with other viruses more likely required oxygen support [adjusted odds ratio (aOR) 1.91 (95% CI: 1.08, 3.39), P = 0.027] than those with AdV-single detection. Children with AdV-C had higher odds of co-detections with other viruses compared with those with AdV-B [aOR 4.00 (95% CI: 1.91, 8.44), P < 0.001]. Conclusion: Clinical differences were identified between AdV-single and AdV co-detected with other viruses, and between AdV-B and AdV-C. Larger studies with AdV typing are needed to determine additional epidemiological and clinical differences between specific AdV species and types.